Komunikasi Informasi & Edukasi Pencegahan Covid-19 Pada Maternal - Hamdiah Ahmar; Catur Yulinawati, Mona Rahayu Putri, Sri Dewi Haryati (JOURNAL OF COMMUNITY DEDICATION, 2021)
Background: Indonesia is still struggling with the Corona virus until now, the same as other countries in the world. The number of cases of the Corona virus continues to grow with some reporting recoveries, but not a few who have died. Handling and prevention efforts continue to be carried out to fight COVID-19 with flu-like symptoms. Objective: to provide CIE and increase knowledge to the community, especially pregnant women in Batam City in preventing COVID-19 in Maternal. Methods: Realization of problem solving in community service activities is carried out through Communication, Information and Education to the CIE community carried out on June 24, 2021 with the main agenda of sharing and educating the community, especially for mothers in recognizing covid 19. The method of activity used to achieve the goals that have been formulated is to first do a pretest around covid 19 then give CIE about COVID-19 using online-based media assisted by the "Knowing Covid -19" booklet which is closed with posttest activities to assess the achievement of the goals of this community service. Result: This activity went smoothly and the success of this activity was seen by the number of questions and enthusiasm of CIE participants as well as increased maternal understanding of covid 19 which can be measured from the client's response.